Static compression test of materials - Ang, Nathanael Shi Wei (2019)
Static Compression Test is a procedure where specimens are subjected to opposing axial forces, forcing the material to be squashed and flattened. The intention of this test method is to identify the material behaviour and properties such as stress, strain, yield strength, compressive strength, and the Young’s modulus under a fixed compressive load at 100kN.